The rural society in Algeria, between the policy of renewal and the participative approach - Baghdad, Chaib (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2015)
The debate on the rural society has always taken some place in some literature and discussing papers, for the fact that some international institutions and organisms have, already, warned about the disastrous situations of the rural spaces, mainly the question of rural poverty, unemployment, precarity, famines, social exclusion, poor social conditions of life and living, and principally, the lack of opportunities to undertake a serious launch of economic development projects, in order to boost the growth and the evolution of such areas to better places and more profitable conditions. It is known that the handling of any subject concerning rural areas is mainly linked to the behavior of the agricultural sector, but also, other professional activities. Our concern is to study how the rural population and actors are dealing with the governmental decision to undertake a wide program to develop the rural regions, called the revival of the rural development, knowing the fact that such population has suffered, for a long time, from the marginalization and exclusion, and voluntary lack of serious projects which has resulted to deteriorating economic and social conditions of life.